The Role of Human Development Index for Women and Wages in Children’s Malnutrition - Azalia, Areta Nur Fatimah; Zakia, Arivia Fikratuz (Jurnal Ilmu Ekonomi Terapan, 2025)
The issues regarding malnutrition in children, including wasting, stunting, and underweight, have raised serious concerns in global public health and economics, particularly in developing countries. This study examined the relationship between women’s human development index and regional minimum wage concerning wasting, stunting, and underweight. It utilized secondary data obtained from BPS (Central Statistics Agency) and used thirty-three provinces in Indonesia from 2018 to 2022, employing panel data regression. The results indicate that the women’s human development index significantly negatively affects stunting and underweight. Additionally, regional minimum wage significantly negatively impacts wasting, stunting, and underweight. These findings underscore the importance of policies supporting improving the Human Development Index for women and establishing a fair regional minimum wage to combat malnutrition issues. Interventions could include preventing anemia in adolescent girls by providing iron supplements, facilitating pregnancy check-ups, providing supplementary food for pregnant women, and offering social assistance for constructing latrines and meeting the nutritional needs of toddlers.